miR-873a-5p Targets A20 to Facilitate Morphine Tolerance in Mice - Huang, Jiangju; Liang, Xia; Wang, Jian; Kong, Yan; Zhang, Zengli; Ding, Zhuofeng; Song, Zongbin; Guo, Qulian; Zou, Wangyuan (Frontiers in Neuroscience, 2019)
Long-term morphine administration leads to tolerance and a gradual reduction in analgesic potency. Noncoding microRNAs (miRNAs) modulate gene expression in a posttranscriptional manner, and their dysregulation causes various diseases. Emerging evidence suggests that miRNAs play a regulatory role in the development of morphine tolerance. In the present study, we hypothesized that miR-873a-5p is a key functional small RNA that participates in the development and maintenance of morphine tolerance through the regulation of A20 (tumor necrosis factor α-induced protein 3, TNFAIP3) in mice. We measured the percentage of maximum possible effect (MPE %) to evaluate the analgesic effect of morphine. The expression of miR-873a-5p and its target gene A20 were determined after the morphine-tolerant model was successfully established. Intrathecal injection with lentivirus to intervene in the expression of A20 and the miR-873a-5p antagomir was used to explore the role of miR-873a-5p in the development of morphine tolerance. Chronic morphine administration significantly increased the expression of miR-873a-5p, which was inversely correlated with decreased A20 expression in the spinal cord of morphine-tolerant mice. Downregulation of miR-873a-5p in the spinal cord attenuated and partly reversed the development of morphine tolerance accompanied by overexpression of A20. Similarly, A20 was upregulated by a recombinant lentivirus vector, which attenuated and reversed the pathology of morphine tolerance by inhibiting the activation of nuclear factor (NF)-κB. Collectively, our results indicated that miR-873a-5p targets A20 in the spinal cord to facilitate the development of morphine tolerance in mice. Downregulating the expression of miR-873a-5p may be a potential strategy to ameliorate morphine tolerance.